Cauca: megafaunal and felid fossils (Mammalia) from a Pleistocene site in northwest Venezuela - Jorge Domingo Carrillo-Briceño; Damián Ruiz-Ramoni; Rodolfo Sánchez; Arturo Jaimes; Edwin Chávez-Aponte; Francisco Juan Prevosti; Valentina Segura; Alfredo Armando Carlini; Lisa Garbé; Olivier Tombret; Antoine Zazzo; Marcelo Ricardo Sánchez-Villagra (Fossil Record, 2024)
Numerous surveys and three excavation and surface collection field seasons resulted in the discovery of numerous megafaunal remains and that of a medium-sized felid in a new site located on the coastal plain of the Gulf of Venezuela, in Western Falcón State. The faunal assemblage is represented by South American natives such as megatheres (cf. Eremotherium laurillardi), an indeterminate mylodontid and a glyptodont (probably related to Glyptotherium) and Nearctic representatives such as gomphotheres (Notiomastodon platensis), equids (Equus sp.) and a feline (Felidae cf. Leopardus pardalis), providing novel information for the distribution of some of these mammals. Radiocarbon indicates that this deposit is at least 40,000 years old. Lithic artefacts of a kind reported for other Pleistocene sites in the region document the presence of humans in Cauca, but as these cultural remains were found on the surface, their association with the fauna is uncertain.